2001
DOI: 10.1021/bm010006w
|View full text |Cite
|
Sign up to set email alerts
|

Degradation of Mannan I and II Crystals by Fungalendo-β-1,4-Mannanases and a β-1,4-Mannosidase Studied with Transmission Electron Microscopy

Abstract: We have used the endo-beta-1,4-mannanase from Trichoderma reesei (Tr Man5A), the endo-beta-1,4-mannanase from Aspergillus niger (An Man5A) and the exo-beta-1,4-mannosidase from A. niger (An Mnd2A) to follow the enzymatic degradation of mannan I and II crystals. The degradation process was studied by transmission electron microscopy and also followed by analysis of the released soluble reducing sugars. The mannan crystals were degraded by the endo-beta-1,4-mannanases and to a lesser extent by the exo-beta-1,4-m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
3
2
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…35 To prepare the nanocrystals, xylan was dispersed in DMSO by using magnetic stirring at 60 ˚C (Figure S1B). After suspending xylan in DMSO at 60 ˚C for 10 days, an elongated flake-like structure was observed under AFM imaging (Figure 2A), similar to precipitates of low molecular weight cellulose 37,38 or mannan 29,30 . The anisotropic shape of the nanostructure is due to a faster growth along one direction.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…35 To prepare the nanocrystals, xylan was dispersed in DMSO by using magnetic stirring at 60 ˚C (Figure S1B). After suspending xylan in DMSO at 60 ˚C for 10 days, an elongated flake-like structure was observed under AFM imaging (Figure 2A), similar to precipitates of low molecular weight cellulose 37,38 or mannan 29,30 . The anisotropic shape of the nanostructure is due to a faster growth along one direction.…”
Section: Resultsmentioning
confidence: 97%
“…22,23 However, hemicellulose, a major part of lignocellulosic biomass, 24 has not been investigated from the point of view of nanocrystals andalthough they do existeven the reports on its crystallization are scarce. 25,26,27,28,29,30 Hemicellulose is generally considered to be amorphous due to the side groups 31 and therefore, its proposed applications have been mainly in bulk applications, for example, films for packaging and coating. 32,33,34 The difficulty to construct controlled, nano-sized crystalline structures, such as rods or fibrils, from hemicellulose has largely impeded its use in more sophisticated materials applications so far.…”
Section: Introductionmentioning
confidence: 99%
“…For example, in Talaromyces cellulolyticus the approximately 80% mannose yield was increased with high β-mannanase and β-mannosidase activities when supplemented with A. niger derived commercial enzyme (Inoue et al, 2015). It has been shown that the crystal of mannan can be degraded when endo-α-1,4-mannanase from T. reesei , endo-α-1,4-mannanase from A. niger and exo-α-1,4-mannosidase from A. niger are used (Hagglund et al, 2001). To evaluate the effects of N-glycan processing on protein secretion, in this study we further analyzed cellulase and β-mannanase activities in Tr-MsdS strain.…”
Section: Discussionmentioning
confidence: 99%
“…For example, in Talaromyces cellulolyticus the approximately 80% mannose yield was increased with high β-mannanase and β-mannosidase activities when supplemented with A. niger derived commercial enzyme [42]. It has been shown that the crystal of mannan can be degraded when endo-α-1,4-mannanase from T. reesei, endo-α-1,4-mannanase from A. niger and exo-α-1,4-mannosidase from A. niger are used [43]. To evaluate the effects of N-glycan processing on protein secretion, in this study we further analyzed cellulase and β-mannanase activities in Tr-MsdS strain.…”
Section: Discussionmentioning
confidence: 99%